Heavy metals uptake by trees near a waste incinerator - Morichetti, Mauro; Passerini, Giorgio; Baltrėnas, Pranas; Baltrėnaitė, Edita; Corvatta, Gianni (International Conference “Environmental Engineering”, 2017)
Incinerators produce energy burning virtually everything including waste, but emit pollutants such as heavy metals and carbon monoxide (CO). These substances can be uptaken by trees through their roots, leaves or stems. To evaluate the quantity of heavy metals uptaken, and to validate the methodology, we studied an incinerator and its area of influence. In order to catalogue the impact of the incinerator on the environment, sampling sites were grouped into seven categories according to the prevailing wind direction. The selected tree species was Populus Alba and heavy metals considered were antimony (Sb), arsenic (As), cadmium (Cd), cobalt (Co), chromium (Cr), nickel (Ni), lead (Pb), copper (Cu), vanadium (V), and zinc (Zn). In a first stage, the metals concentrations were compared with literature data. Metals with higher concentrations were chromium (Cr) and lead (Pb). Metal concentrations of polluted zones were then compared, with control site. Sample points near the incinerator showed lower metals concentrations whereas, all samples taken in an urban area had higher concentrations, especially chromium (Cr) and lead (Pb). A final analysis revealed that the tree species chosen are not a good choice to evaluate bioaccumulation since its dynamic factors of biophilicity are low. However such trees proved suitable for phytoremediation.